In the Sultan's Salon: Learning, Religion, and Rulership at the Mamluk Court of Qāniṣawh al-Ghawrī (r. 1501-1516) (2 vols) - Mauder, Christian, (Islamic History and Civilization ;, 2021)
Christian Mauder's In the Sultan's Salon builds on his award-winning research and constitutes the first detailed study of the Egyptian court culture of the Mamluk Sultanate (1250-1517). Based mainly on understudied Arabic manuscript sources describing the learned salons of the Mamluk Sultan al-Ghawrī, In the Sultan's Salon presents the first theoretical conceptualization of the term "court" that can be fruitfully applied to premodern Islamic societies. It uses this conceptualization to demonstrate that al-Ghawrī's court functioned as a transregionally interconnected center of dynamic intellectual exchange, theological debate, and performance of rule that triggered novel developments in Islamic scholarly, religious, and political culture.